Integration of Reproductive Health Values in Islamic Religious Education Learning for Upper Elementary School Students - Tri Ermayani; Sukiman; Sigit Purnama; Sibawaihi; Norhapizah Mohd Burhan (Indonesian Values and Character Education Journal, 2025)
Reproductive health knowledge is a crucial element for improving individual quality of life and wellbeing, including among elementary school students. However, students’ understanding of this topic remains limited, putting them at risk of issues such as unintended pregnancy, sexually transmitted infections, and early marriage. This study aims to analyze strategies for integrating reproductive health values into Islamic Religious Education (IRE) learning for elementary school students. A descriptive-analytic qualitative method was employed, with data collected through interviews, observations, and document studies. Thematic analysis was conducted to identify patterns and integration strategies. The results indicate that integration is implemented through four main strategies: linking puberty with the concept of akil baligh, associating organ health with hifzh al-nafs, integrating risk behaviors with hifzh al-nasl and aurat, and connecting healthy communication with social etiquette. Effective learning methods include interactive lectures, storytelling, role play, and project based assignments. Challenges identified include limited teacher competence, lack of integrated teaching materials, and topic sensitivity. The study concludes that a systemic approach involving teacher training, module development, and parental involvement is essential. The implications suggest that integrating reproductive health values based on Islamic principles can enhance cognitive understanding, foster character development, strengthen healthy behaviors, and serve as a reference for the holistic development of Islamic Religious Education curricula.